Liquidity, capital structure, and firm value effects on profitability: evidence from plantation companies listed on the Indonesian stock exchange - Melani Melani; Suhardi Suhardi; Nadia Sri Rejeki (Economic: Journal Economic and Business, 2026)
This study aims to analyze the effect of liquidity, capital structure, and firm value on the profitability of plantation companies listed on the Indonesia Stock Exchange for the 2020–2024 period. The study used a quantitative approach with panel data from 24 companies, resulting in 120 observations. The research variables were measured using the Current Ratio (CR), Debt to Equity Ratio (DER), Price to Book Value (PBV), and Return on Assets (ROA). The analysis was conducted using panel data regression using the Chow, Hausman, and Lagrange Multiplier tests. The results showed that liquidity had a positive and significant effect on profitability, demonstrating the importance of working capital management in improving a company's operational efficiency. Capital structure had a negative but insignificant effect on profitability due to high financial risk and interest expenses. Meanwhile, firm value did not have a significant effect on profitability because market perception does not directly reflect the operational performance of plantation companies. This study confirms that liquidity management is a key factor in improving the profitability of plantation companies.